Development of Volleyball Learning Application: Fun Volley by Using Augmented Reality Technology - Khoo Yi Zhe,; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2023)
Volleyball is one of the sports included in secondary school physical education (PE) subjects, specifically in Form 1 and Form 4 syllabi. However, the limited media in textbooks causes the loss of student interest in learning theoretical volleyball knowledge while the limited content cannot ensure the effectiveness of delivery of the whole subject matter. Therefore, this project proposes the development of a volleyball learning application named Fun Volley. The purpose of this Fun Volley application is to help volleyball learners to learn the fundamentals of volleyball using markerless augmented reality (AR) technology. Multimedia Mobile Content Development (MMCD) approach is used to develop the Fun Volley application. The user acceptance test shows a 72.98% average score for the developed application based on the System Usability Scale and more than 70% of positive feedback with the Technology Acceptance Modal. The future works included adding more AR elements and additional exercise modules.